Microstructural Characteristic of Dissimilar Welded Components (AISI 430 Ferritic-AISI 304 Austenitic Stainless Steels) by CO2 Laser Beam Welding (LBW) - Caligulu, Ugur; Dikbas, Halil; Taskin, Mustafa (Gazi Univ, 2012)
In this study, microstructural characteristic of dissimilar welded components (AISI 430 ferritic-AISI 304 austenitic stainless steels) by CO2 laser beam welding (LBW) was investigated. Laser beam welding experiments were carried out under argon and helium atmospheres at 2000 and 2500 W heat inputs and 100-200-300 cm/min. welding speeds. The microstructures of the welded joints and the heat affected zones (HAZ) were examined by optical microscopy, SEM, EDS and XRD analysis. The tensile strengths of the welded joints were measured. The result of this study indicated that; the width of welding zone and HAZ became much thinner depending on the increased welding speed, on the other hand, this width become wider depending on the increased heat input. Tensile strength values also confirmed this result. The best properties were observed at the specimens welded under helium atmosphere, at 2500 W heat input and at 100 cm/min welding speed.
Keywords: Ferritic Stainless Steel (AISI 430); Austenitic Stainless Steel (AISI 304); CO2 Laser Beam Welding; Microstructural Characteristic